(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hospital-acquired infections (HAIs) in Enterococcus fecium (VREfm) are primarily caused by the resistant to vancomycin vanA gene, which confers high-level resistance to vancomycin. With an emphasis on quantitative PCR (qPCR) and loop-mediated isothermal amplification (LAMP) for vanA detection, this review delves deeply into the epidemiology, molecular mechanisms, and diagnostic challenges of VREfm. We explore their applications using case studies, mutation analyses, and gene prevalence computational data. The benefits and drawbacks of LAMP and qPCR in clinical contexts are carefully considered. Two tables provide a summary of vanA mutation and VREfm prevalence data from recent studies. By combining data from around the globe to guide infection control and diagnostic approaches, the review tackles the urgent need to address the public health threat posed by VREfm. Future directions like CRISPR-based diagnostics and next-generation sequencing (NGS) are also explored.